The Conceptual Connections for Solving Trigonometric Equations - Maphutha, Kgaladi; Mutodi, Paul; Phele, Elizabeth Chuene (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2025)
The study explored Grade 11 learners conceptual connections ability as they solve trigonometric equations. A case study design within a qualitative research approach was used to explore how learners’ conceptual connections ability affected their solution process as they were solving trigonometric equations. Forty-eight (48) conveniently sampled grade 11 learners from a school in Capricorn South District, Limpopo Province of South Africa participated in the study. Data were gathered through written tasks and task-based interviews. Inductive thematic analysis was used to analyse the data. The study's results suggested that the capability of learners to establish connections within mathematics influences the effective solving of trigonometric equations. Learners with conceptual connections ability were able to connect concepts such as trigonometric identities, ratios, rules and appropriate algebraic processes and concepts, procedures as well as representing trigonometric equations using graphs, and tables. Learners who lacked conceptual connections abilities committed procedural and representation errors, and this affected their solution process as they solved trigonometric equations. This study, therefore, recommends that learners’ ability to make connections be enhanced during the teaching and learning process for their conceptual understanding of mathematics topics.